Electronic structure, optical, photocatalytic and charge storage performance of WO3 nanostructures. (June 2022) - Assadullah, Insaaf; Bhat, Aadil Ahmad; Malik, Javied Hamid; Malik, Khurshaid Ahmad; Tomar, Radha; Khandy, Shakeel Ahmad
Abstract: In this paper, we report the fabrication of WO3 nanostructures via hydrothermal route. This is the first report on pristine WO3 nanoparticles being synthesized in a relatively short timed (4h) hydrothermal reaction. The obtained material was characterized in detail by a number of techniques: X-ray powder diffraction, scanning electron microscopy (SEM), optical studies, and Fourier transform analysis. From the observed results, these WO3 nanoparticles exhibit a diameter approximately between 3 and 30 nm. Density functional theory calculations confirm the electronic band gap of 3.4 eV in accordance to experimental band gap obtained from optical absorption spectra. Cyclic voltammetry of the prepared WO3 nanoparticles reveal the exhibition of remarkable electrochemical activity. In addition, the WO3 particles were exposed to phenol and it was observed that 90.8% of phenol was degraded during the reaction time of 1.5 h. According to The International Commission on Illumination (CIE) the synthesized material shows blue emission and is suitable for blue LEDs. Highlights: Rapid synthesis of WO3 nanostructures via hydrothermal route with a diameter of about 3–30 nm is achieved. DFT calculations confirm the electronic band gap of 3.2 eV in accordance to experimental band gap. Degradation of Phenol is observed up to 90% of Phenol during the reaction time of 1.5 h.